The impact of group cohesion on key success measures in higher education. Issue 4 (20th April 2020) - Thornton, Claire; Miller, Phillip; Perry, Kelly
ABSTRACT: Higher education institutions (HEIs) are increasingly being measured using key performance indicators (KPIs) such as student retention, success, achievement and attendance. There is a dearth of research focusing on group dynamics within classroom settings, with very little focusing on cohesion. There is, however, evidence, in organisational and sports settings, that cohesion can have a positive impact upon performance and adherence to group activities. More cohesive classes may therefore result in improved performance in higher education (HE) . This study aimed to examine whether group cohesion was related to markers of student success in higher education (HE) classes in three English colleges. Participants were 107 first-year sports students who completed the Perceived Cohesion Scale for Small Groups (PCS) at the end of semesters one and two. Responses were correlated with student attendance, success, achievement and retention. Results indicated that attendance was positively correlated with cohesion ( r = 0.4, p = 0.01), but no other relationships emerged. The effect sizes were higher in semester two than in semester one, which suggests that cohesion may develop over time in student groups. The findings indicate that cohesion may be important to enhance attendance at colleges and that building cohesion should be a priority for classroom managers.